Kemampuan Deklamasi Puisi pada Siswa SMA Negeri 2 Kampar Kiri Tengah di Penghidupan Kecamatan Kampar Kiri Tengah Kabupaten Kampar - Amanan; Hermansyah; Juswandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2022)
Deklamasi Puisi comes from the Latin 'declare or declaim' which means reading the work in the form of poetry or rhymes accompanied by gestures and songs. Devoting poetry or short story has the meaning of reading. Reading poetry is a form of appreciation and artistic expression. This service activity is held for students of SMA Negeri 2 Kampar Kiri Tengah. Riau Province Government Requires this Reformation has proclaimed to foster and develop Malay culture and Malay culture (BMR) This activity to be held is to improve the ability to recite poetry which is expected to help students at SMA Negeri 2 Kampar Kiri Tengah to interpret/understand, train and practice good poetry reading, so that students at SMA Negeri 2 Kampar Kiri Tengah, with The arrival of the service team from the Faculty of Cultural Sciences, Lancang Kuning University is expected to help the school and especially the students of SMA Negeri 2 Kampar Kiri Tengah to get to know Riau Malay Culture, especially the ability to pronounce.